PENGARUH MANAJEMEN ASET TERHADAP OPTIMALISASI ASET TETAP PEMERINTAH KABUPATEN JAYAPURA - Moses Demetouw; Agustinus Salle; Meinarni Asnawi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
This research aims to analyze the influence of asset management on the level of optimizing fixed assets (land and building) in local governments of Jayapura regency. Using purposive sampling method the sample to this research is 48 respondents. The variables are assets inventory, legal audit assets, asset valuation, and supervision and assets control. According to the results using the multiple linear regression showed that individually inventory assets proven has a positive and significant impact on optimizing fixed assets (land and building) which means in accordance with hypothesis, individually legal audit assets not proved has a positive and significant impact on the level of optimizing assets fixed (land and building) which means not in accordance with hypothesis, individually asset valuation proven have had a positive and significant impact on the level of optimizing assets fixed (land and building), supervision and control assets proven have positive and significant impact on the level of optimizing assets fixed (land and building). While the simultaneous analysis results show that the four variables namely inventory of assets, audit legal assets, asset valuation, supervision and assets control proved significant / give positive response to the level of fixed ground asset optimality (land and building) this is proven by the value of F count > F table. Keyword: assets inventory, assets legal audit, assets valuation, assets supervision and control, optimizing fixed assets (land and building).